Steps of a staircase (Journal of Parents and Teachers, 2014)
Antonio Buero Vallejo was a Spanish playwright, winner of multiple awards such as the Premio Lope de Vega de Teatro or the Premio Nacional de Teatro (three times). This article presents aspects of his plays, his biography and his statements. All this is done alphabetically, without following the actual timeline. The last page proposes an activity about Antonio Buero Vallejo and his plays for teachers.
Keywords: Antonio Buero Vallejo; playwright; biography; plays; theatre